Urban Egyptian Women Aged 19–30 Years Display Nutrition Transition-Like Dietary Patterns, with High Energy and Sodium Intakes, and Insufficient Iron, Vitamin D, and Folate Intakes. Issue 2 (6th January 2020) - Brouzes, Chloé M C; Darcel, Nicolas; Tomé, Daniel; Dao, Maria Carlota; Bourdet-Sicard, Raphaëlle; Holmes, Bridget A; Lluch, Anne
ABSTRACT: Background: Recent changes in Egyptian dietary habits can be attributed to more urban and sedentary lifestyles and to alterations in the dietary and economic context. The mean BMI of Egyptian women is one of the highest worldwide, and 50% have iron deficiency. Objective: The aim was to quantify food and nutrient intakes of urban Egyptian women and conduct a detailed analysis of micronutrients commonly consumed in inadequate amounts, such as iron, vitamin D, and folate. Methods: Urban Egyptian women aged 19–30 y ( n = 130) were recruited during 2016–2017. Energy needs were estimated using the Henry equation, assuming a low physical activity level (1.4). Dietary intakes and iron bioavailability were estimated from a 4-d food diary. Macronutrient intakes were compared with WHO/FAO population goals and micronutrient intakes with Egyptian recommendations. Iron needs were determined for each subject. Results: The mean BMI (kg/m 2 ) was 27.9 ± 4.9. The mean total energy intake (TEI; 2389 ± 715 kcal/d) was significantly higher than needs (2135 ± 237 kcal/d; P = 0.00018). Total fat (33%TEI) and SFA (11%TEI) intakes were slightly higher than population goals (15–30%TEI and <10%TEI, respectively). Diets provided 18 ± 8 g/d of fiber, 98 ± 54 g/d of total sugars, and nearly twice the recommended sodium intake (intake: 2787 ± 1065 mg/d; recommendation: <1500 mg/d). Estimated dietary iron bioavailability was low (9.2% ± 1.6%), and 79% of women consumed less iron than the average requirement (17.5 ± 7 mg/d). Overall, 82% and 80% of women consumed less vitamin D and folate, respectively, than recommended. Conclusions: Egyptian women aged 19–30 y have high intakes of energy and sodium, whereas iron, vitamin D, and folate intakes are insufficient, with only low concentrations of bioavailable iron. These results call for further investigation into measures that would improve this population's diet quality.